2020
DOI: 10.15252/embj.2019104081
|View full text |Cite
|
Sign up to set email alerts
|

Highly active rubiscos discovered by systematic interrogation of natural sequence diversity

Abstract: CO2 is converted into biomass almost solely by the enzyme rubisco. The poor carboxylation properties of plant rubiscos have led to efforts that made it the most kinetically characterized enzyme, yet these studies focused on < 5% of its natural diversity. Here, we searched for fast‐carboxylating variants by systematically mining genomic and metagenomic data. Approximately 33,000 unique rubisco sequences were identified and clustered into ≈ 1,000 similarity groups. We then synthesized, purified, and biochemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(150 citation statements)
references
References 65 publications
8
142
0
Order By: Relevance
“…This result is also compatible with the mechanistic models of RuBisCO (Farquhar, 1979), and is supported by the recent discovery of enzyme variants which exhibit the highest kcatC ever recorded at the expense of poor CO2 affinities (i.e. KC values >250 µM) (Davidi et al, 2020). Nevertheless, the dependency between CO2 affinity and turnover, despite being the strongest pairwise correlation between kinetic traits observed, is still only partial (~30 % variance explained), and is substantially attenuated relative to the coefficients conventionally cited from studies investigating limited numbers of species (Tcherkez, Farquhar and Andrews, 2006;Savir et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…This result is also compatible with the mechanistic models of RuBisCO (Farquhar, 1979), and is supported by the recent discovery of enzyme variants which exhibit the highest kcatC ever recorded at the expense of poor CO2 affinities (i.e. KC values >250 µM) (Davidi et al, 2020). Nevertheless, the dependency between CO2 affinity and turnover, despite being the strongest pairwise correlation between kinetic traits observed, is still only partial (~30 % variance explained), and is substantially attenuated relative to the coefficients conventionally cited from studies investigating limited numbers of species (Tcherkez, Farquhar and Andrews, 2006;Savir et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…For kinetic measurements of diverse rubiscos, see recent meta-analyses by Flamholz et al, 2019 ; Iñiguez et al, 2020 . For recent measurements of the R. eutropha , R. rubrum , and S. elongatus enzymes, see Davidi et al, 2020 ; Occhialini et al, 2016 ; Satagopan and Tabita, 2016 . ( B ) Growth rate and yield of CCMB1:p1A+vec depend on the CO 2 concentration, with higher CO 2 improving growth (‘vec’ denotes pFA-sfGFP).…”
Section: Resultsmentioning
confidence: 99%
“…Net carboxylation was calculated as the carboxylation rate less ½ the oxygenation rate, which presumes a plant-type photorespiratory pathway that loses one CO 2 for every two oxygenation reactions. ( B ) Bacterial Form II rubiscos are typically found in organisms living in low O 2 environments and, accordingly, display low CO 2 specificities (S C/O ≈ 10) and relatively high maximum carboxylation rates (k cat,C ≈10–20 s −1 , Davidi et al, 2020 ). As such, Form II rubiscos do not perform well in ambient CO 2 and O 2 concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This was illustrated in dramatic fashion when a single study reported 1,003 reference genomes selected solely because they maximized coverage of phylogenetic space, and which collectively increased the number of known protein sequence families by over 10% 11 . Sequence similarity networks and genome mining algorithms are also being used increasingly to identify enzymes with divergent sequences that expand our understanding, have biotechnological value, or both 13,28–32 . For example, a recent study identified 33,000 sequences for the carbon‐fixing enzyme, ribulose‐1,5‐bisphosphate carboxylase/oxygenase (RuBisCO), in genomic and metagenomic datasets 28 .…”
Section: Resultsmentioning
confidence: 99%